2016 IEEE International Reliability Physics Symposium (IRPS) 2016
DOI: 10.1109/irps.2016.7574610
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reliability of a hard-switched boost power processing unit utilizing SiC power MOSFETs

Abstract: Silicon carbide (SiC) power devices have demonstrated many performance advantages over their silicon (Si) counterparts. As the inherent material limitations of Si devices are being swiftly realized, widebandgap (WBG) materials such as SiC have become increasingly attractive for high power applications. In particular, SiC power metal oxide semiconductor field effect transistors' (MOSFETs) high breakdown field tolerance, superior thermal conductivity and low-resistivity drift regions make these devices an excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Leveraging advanced component models and SPICE simulations, a normalized system efficiency is represented in Figure 9. Results from clamped inductive switching tests conclude negligible variation in switching energy for devices with increasing junction temperature and is assume constant [14]. However, due to the susceptibility to gate oxide leakage and on-state resistance drift at high temperature the conduction loss in the MOSFETs does not remain constant over the observed temperature range.…”
Section: B System Efficiencymentioning
confidence: 93%
“…Leveraging advanced component models and SPICE simulations, a normalized system efficiency is represented in Figure 9. Results from clamped inductive switching tests conclude negligible variation in switching energy for devices with increasing junction temperature and is assume constant [14]. However, due to the susceptibility to gate oxide leakage and on-state resistance drift at high temperature the conduction loss in the MOSFETs does not remain constant over the observed temperature range.…”
Section: B System Efficiencymentioning
confidence: 93%
“…The increase of R DS_ON in the dose range from 20 to 700 kGy is not so critical. Tenfold increase in R DS_ON causes only 5% decrease in efficiency of a power converter such as shown in work where the 1200 V SiC MOSFET was used as an active switch.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the number of parts tested is also dependent on the acceleration factor and for obtaining the required failure metrics at stress values close to the nominal gate voltage required very large sample numbers [30]. Examples of lifetime calculations for SiC MOSFETs are available in [24,26,31]. In [31], accelerated gate stresses were performed at different temperatures and the data indicated that reducing the gate voltage from 20.588 V to 19.127 V improved the predicted lifetime of the gate oxide from 10 to 20 years for a temperature of operation of 150 °C.…”
Section: Gate Oxide Lifetime and Reliability Considerationsmentioning
confidence: 99%
“…Examples of lifetime calculations for SiC MOSFETs are available in [24,26,31]. In [31], accelerated gate stresses were performed at different temperatures and the data indicated that reducing the gate voltage from 20.588 V to 19.127 V improved the predicted lifetime of the gate oxide from 10 to 20 years for a temperature of operation of 150 °C. The studies in [24] used a previous generation of the device evaluated in this paper and from the lifetime projections, reducing the gate driver voltage 10% (from 20 V to 18 V) increases the lifetime approximately 3.6 times.…”
Section: Gate Oxide Lifetime and Reliability Considerationsmentioning
confidence: 99%